Hypoxia-induced let-7f-5p/TARBP2 feedback loop regulates osteosarcoma cell proliferation and invasion by inhibiting the Wnt signaling pathway - Chen, Guangnan (Aging (Albany NY), 2020)
Osteosarcoma (OS) is the most common bone tumor in children and adolescents and is characterized by high metastatic and recurrence rates. In the past, it has been shown that microRNAs may play critical roles in hypoxia-related OS proliferation and invasion. However, the mechanisms by which OS cells acquire this malignant phenotype have remained largely unknown. In the present study, we report that let-7f-5p and TARBP2 were expressed in lower amounts in human OS cell lines when compared with the hFOB normal human osteoblastic cell line; however, both types of cells were repressed by hypoxia. let-7f-5p and TARBP2 significantly inhibited the proliferation and invasion of OS cells. Furthermore, TARBP2 as a downstream and functional target of let-7f-5p regulated the expression of let-7f-5p, and there was a regulatory feedback loop between let-7f-5p and TARBP2. This loop reduced the expression of let-7f-5p and TARBP2 in OS cells to a very low level, which was induced by hypoxia. Furthermore, the hypoxia-induced let-7f-5p/TARBP2 feedback loop contributed to activation of the Wnt signaling pathway. Taken together, our data clearly showed that the feedback loop between let-7f-5p and TARBP2 induced by the hypoxia-promoted OS cell malignant phenotype increased with activation of the Wnt signaling pathway.